The new real estate investment trusts in Malaysia : lessons from listed property trusts - Lee, Yim Mei Janice (2005)
Institutional investors hold significant equity levels in overseas Real Estate Investment Trusts (REITs) and evidence reveals that their active participation brings tremendous benefits to the REIT markets. In Malaysia however, the level of institutional investment have historically been rather poor since the establishment of the first Listed Property Trust (LPTs) in 1989. Nowadays, interests in REITs are renewed in Malaysia due to encouraging government incentives and the revised regulations in Securities Commission Guidelines 2005. Axis REIT is listed and a number of REITs are planned for listing by corporations with large property portfolios in the near future. As the investment market welcomes exciting new opportunities, it is timely to consider the needs of institutional investors in Malaysia on the new REITs. This paper examines the reasons of lukewarm response from institutional investors in LPTs and their desirable investment conditions for participating in the new REITs. Finally, the intended actions from corporations planning to list REITs are obtained in response to the institutional investors’ needs. The findings from the paper depicts that the thin trading volume of LPTs, small market size of LPT market and slow capital appreciation are the main reasons deterring institutional involvement in LPTs market.